Stress induced hypercortiksteronemia in pregnant female rats – cause of hypoleptinemia in newborn offspring and their predisposition to obesity - Perets, O. V.; Sergiyenko, L. Yu. (Journal of Education, Health and Sport, 2017)
In the experiment on Wistar rats, the body weight and weight of visceral adipose tissue in the were determined in intact offspring as compared with offspring gestationally from stressed mothers which were born with low body weight. It is shown that in adult descendants of stressed mothers the body weight and mass of visceral adipose tissue are larger in comparison with descendants of intact mothers. At the same time, the descendants of stressed mothers do not differ from intact in terms of the amount of food consumed. It is conducted a comparative study of the histological structure of adipose tissue in female rats - the descendants of intact and gestationally stressed mothers in the basal state and after the action of stress. It was found that the aging of mature offspring results in the formation of a hypertrophic type of obesity in intact animals and provokes hyperplasia of adipocytes and inflammation of adipose tissue in rats strained in the antenatal period.